2008
DOI: 10.1051/0004-6361:200809635
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved spectroscopy of planetary nebulae and their halos

Abstract: Strong mass loss off stars at the tip of the asymptotic giant branch (AGB) profoundly affects properties of these stars and their surroundings, including the subsequent planetary nebula (PN) stage. With this study we wanted to determine physical properties of mass loss by studying weakly emitting halos, focusing on objects in the galactic disk. Halos surround the, up to several thousand times, brighter central regions of PNe. Young halos, specifically, still contain information of the preceeding final mass los… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 86 publications
2
53
1
Order By: Relevance
“…Typical values needed for the final AGB mass-loss rates areṀ agb 10 −4 M yr −1 with wind velocities between about 10−15 km s −1 . Values of about 10 −4 M yr −1 for the final AGB mass-loss rates from four well-known Galactic PNe have recently been derived by Sandin et al (2008) using integral field spectroscopy of the respective PN haloes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical values needed for the final AGB mass-loss rates areṀ agb 10 −4 M yr −1 with wind velocities between about 10−15 km s −1 . Values of about 10 −4 M yr −1 for the final AGB mass-loss rates from four well-known Galactic PNe have recently been derived by Sandin et al (2008) using integral field spectroscopy of the respective PN haloes.…”
Section: Discussionmentioning
confidence: 99%
“…Marten (1993aMarten ( , 1995 demonstrated that non-equilibrium may become important for rapidly expanding, low-density nebular shells, and also for cases with quickly evolving central stars. Well-known examples are the hot PN haloes that are extremely out of thermal and ionisation equilibrium (Marten 1993b;Sandin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 14 we show wavelength-calibrated and flat-fielded spectra of data of LARR and PPAK from the central regions of two planetary nebulae: NGC 2392 for PPAK and M 2-2 for LARR, whose outcome is presented in Sandin et al (2008). In the first case we reduced the LARR data using MOX (without correcting for cross-talk) and aperture extraction.…”
Section: Accuracy Of Spectra Extracted Using the Three Different Methodsmentioning
confidence: 99%
“…The required information is mostly found in the data header. For more details on this issue see Sandin et al (2008) and the spatial interpolation procedure of Arribas et al (1999).…”
Section: Object Extractionmentioning
confidence: 99%
“…This can be tessellated a posteriori, preserving the relevant spatial information as best possible, but at the same time optimizing the quality of the signal by co-adding the spectra belonging to a given portion of the mapped area -the tile -(e.g. Monreal-Ibero et al 2005;Sandin et al 2008). Here, we use this principle to explore the capabilities of MUSE to obtain spatially resolved information of extragalactic DIBs.…”
Section: Introductionmentioning
confidence: 99%